Group dynamics: a strategy for meaningful learning at the university - Muñoz-Pérez, Soraya (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2023)
Today’s society requires the university to prepare professionals who are trained in all dimensions of the person. This paper shows a didactic strategy that helps to promote meaningful learning in higher education students. Starting from the development of a group dynamics, the necessary collaborative work conditions are generated to involve students in the construction of the contents of a subject, as well as to develop transversal competences necessary for academic and personal life.